PSYCHOMETRIC PROPERTIES OF FACULTY PERFORMANCE EVALUATION INSTRUMENT OF STATE UNIVERSITIES AND COLLEGES IN THE PHILIPPINE EASTERN VISAYAS REGION - Donald M. Patimo (Jurnal Evaluasi Pendidikan, 2020)
The main concern of this study was the assessment of the faculty performance evaluation instrument of State Universities and Colleges in the Philippine Eastern Visayas Region. Specifically, the study sought answers to research questions on what are the psychometric properties of the evaluation instrument and what are the problems identified with regards to the faculty performance evaluation instrument. In search of answers to the abovementioned research questions, the researcher made use of the descriptive-assessment research design. The respondents of this study were administrators, faculty members, and students from the main campuses of State Universities and Colleges in Philippine Eastern Visayas Region. As result, the researcher found out that the faculty performance evaluation instrument of the SUCs was valid and administrable, but not yet tested for reliability. The serious problems identified on the faculty performance evaluation system of SUCs in Philippine Eastern Visayas Region were primarily related to the evaluation criteria and procedure such as the lack of involvement of administrators, faculty, and students in the construction of the evaluation system.